Carminda Cavaco: pioneer of tourism studies in Portugal - Sarmento, João (2018)
On a cold and misty winter morning we were warmly greeted by Carminda Cavaco on her Lisbon apartment. Serenely on her couch, lighting a cigarette at regular intervals, Carminda happily answered our endless questions and calmly (re)counted various episodes of her life. We chatted for about three hours, scribbling some notes hastily, and travelled to her youth, to her voyages and initial papers, to the development of her early career, attempting to understand the paths that brought her to become the pioneer and the most influential Portuguese academic in the field of tourism. Some weeks earlier, from the other end of the Mediterranean, Metin Kozak approached us to write her portrait, an idea to which we were immediately attracted. Both authors are part of the same research group as Carminda – TERRITUR, Centre for Geographical Studies, University of Lisbon – and while one of us (João) is a geographer with interests in tourism like herself, the other (Ana) has a background in tourism management, communication and geography, has worked with her since 1998 in various research projects and publications (Inácio & Cavaco, 2010; Inácio & Joaquim, 2008), and is one of her few former PhD students (Inácio, 2008). Despite all our enthusiasm, we quickly realised that condensing almost 50 years of intense scholarship and publications in the field of tourism into a short paper like this would not be an easy task. Yet, it is critical to write a profile for an international audience. Firstly because Carminda’s CV and academic path eludes most google endeavours. Secondly, since most of her published works are not in English (remarkable exceptions are Cavaco, 1993a, 1995b, 1995c). Thirdly, because the only publication that comprehensively reviews and analyses her life and work in detail, and perhaps the single printed document with some biographic information on Carminda Cavaco, was published in Portuguese by Luís Moreno, one of her former PhD students, on the occasion of her jubilation, ten years ago (Moreno, 2006).